استنباطِ احکام میں ضعیف حدیث کا مقام اور فقہاء کی آراء کا تجزیاتی مطالعہ: Analytical study of the Status of hadith e Da’eef in the interpretation of rulings and the opinions of the jurists - Abbas, Yasir (Al-Amīr Research Journal for Islamic Studies, 2023)
There are two main sources of Islam, one is the Book of Allah and the other is the Sunnah and Sira of the Prophet (peace be upon him). The Qur’an is the final collection of 23 years of divine revelation revealed to the Holy Prophet (PBUH) whose literal and spiritual preservation was undertaken by Allah Almighty Himself. Therefore, the Qur’an is the only book in the world which has one letter, one action and one line in its original state just as it was revealed to the pure heart of the Holy Prophet (sws) and the Holy Prophet (sws). The Prophet (peace and blessings of Allaah be upon him) told the Sahaabah. That is why the greatest truth of Islam, the book is the living Qur’an. The second major basis of the reality of Islam is the pure Sira and Sunnah of the Prophet of Humanity, the Servant of the Universe. Like the Qur’an al-Hakim, every moment, every day and every angle of the life of the author of the Qur’an is in front of everyone like an open book with all its mysteries. Even in front of one’s own and in front of others. A da’if hadith is a hadith which does not fulfil the conditions of the sahih or hassan hadith. Ruling: There is a difference of opinion between the ‘ulema on the ruling on acting upon weak hadiths. The reliable opinion is that weak hadiths can be acted upon for virtuous supererogatory deeds (fada’il al a’mal), for religious exhortation, and stories, and similar things that are not connected to legal rulings and tenants of belief. Keywords: Hadith, Hadith e Da’eef, Derivation of Ahkaam, Jurists, Different opinions.